Comorbidity of Allergic and Autoimmune Diseases Among Patients With ADHD: A Nationwide Population-Based Study. (February 2017) - Chen, Mu-Hong; Su, Tung-Ping; Chen, Ying-Sheue; Hsu, Ju-Wei; Huang, Kai-Lin; Chang, Wen-Han; Chen, Tzeng-Ji; Bai, Ya-Mei
Objective: Patients with ADHD have been suggested to have increased risks of allergic diseases but without consistent results, and limited studies about the association between ADHD and autoimmune diseases were noted in the literature.Method: Utilizing the Taiwan National Health Insurance Research Database, ADHD patients were identified and compared with age- and gender-matched controls (1:4).Results: In all, 8, 201 participants were identified as having ADHD, and an increased prevalence of allergic diseases, including asthma (odds ratio [OR] = 1.53), allergic rhinitis (OR = 1.59), atopic dermatitis (OR = 1.53), and urticaria (OR = 1.39), compared with the control group. Although the comorbidity of autoimmune diseases with ADHD was low, ADHD patients had a significantly greater prevalence of ankylosing spondylitis (OR = 2.78), ulcerative colitis (OR = 2.31), and autoimmune thyroid disease (OR = 2.53) than the controls.Conclusion: Our results supported the association between ADHD and allergic/autoimmune diseases. The further studies will be required to clarify the underlying mechanisms.